Heteronuclear bipyrimidine-bridged Ru-Ln and Os-Ln dyads: low-energy 3MLCT states as energy-donors to Yb(III) and Nd(III). - Lazarides, T; Adams, H; Sykes, D; Faulkner, S; Calogero, G; Ward, MD (2008)
The complexes [Ru((t)Bu(2)bipy)(bpym)X(2)] (X = Cl, NCS) and [M((t)Bu(2)bipy)(2)(bpym)][PF(6)](2) (M = Ru, Os) all have a low-energy LUMO arising from the presence of a 2,2'-bipyrimidine ligand, and consequently have lower-energy (1)MLCT and (3)MLCT states than analogous complexes of bipyridine. The vacant site of the bpym ligand provides a site at which [Ln(diketonate)(3)] units can bind to afford bipyrimidine-bridged dinuclear Ru-Ln and Os-Ln dyads; four such complexes have been structurally characterised. UV/Vis and luminescence spectroscopic studies show that binding of the Ln(III) fragment at the second site of the bpym ligand reduces the (3)MLCT energy of the Ru or Os fragment still further. The result is that in the dyads [Ru((t)Bu(2)bipy)X(2)(mu-bpym)Ln(diketonate)(3)] (X = Cl, NCS) and [Os((t)Bu(2)bipy)(2)(mu-bpym)Ln(diketonate)(3)][PF(6)](2) the (3)MLCT is too low to sensitise the luminescent f-f states of Nd(III) and Yb(III), but in [Ru((t)Bu(2)bipy)(2)(mu-bpym)Ln(diketonate)(3)][PF(6)](2) the (3)MLCT energy of 13,500 cm(-1) permits energy transfer to Yb(III) and Nd(III) resulting in sensitised near-infrared luminescence on the microsecond timescale.